Pengaruh Pelatihan Hemlich Manuver Terhadap Keterampilan Ibu Dalam Penanganan Tersedak Pada Anak Di Posyandu Desa Klumprit - Alifia Susilowati Yanuar; Sahuri Teguh Kurniawan; Lalu M Panji Azali (An-Najat, 2024)
Children are at high risk of choking due to their high level of mobility and limited awareness of the hazard. Choking in children is an emergency that requires immediate treatment to prevent oxygen deprivation and death. This study aimed to evaluate the effect of Heimlich Maneuver training on mothers' skills in managing choking cases at the Posyandu Klumprit Village. The method employed quantitative research with a pseudo-experimental design. The sample consisted of 75 mothers with children aged 2-5 years, who were selected using purposive sampling. The results revealed that 89.3% of mothers had low skills in handling choking before the training. However, 84% of mothers significantly improved their skills after the training. The Wilcoxon test indicated that the training significantly improved mothers' skills (p-value = 0.000). These findings suggested that Heimlich Maneuver training is efficacious in enhancing mothers' skills in addressing child choking cases, which contributes to improving children's safety.